Utilização de uma formulação de cloxacilina nanoestruturada para o tratamento da ceratoconjuntivite infecciosa bovina - Maia, Júlia Marques da Silva (2015)
The infectious bovine keratoconjunctivitis (IBK) is an important ocular disease of cattle. One of the great challenges of IBK is its treatment, given that both topical and parenteral formulations present several drawbacks. The application of parenteral drugs has a longer grace period and may leave residues in milk and meat. The topical application is often precluded by handling difficulty, since many applications are required. In order to circumvent treatment limitations, we evaluated the use of a nanostructured formulation of cloxacillin. The IBK was experimentally induced in 46 calves, both pure and crossbred, homogeneously divided into 3 groups according to blood degree. One group (n = 16) was treated with a suspension of cloxacillin nanoparticles, and another (n = 13) received an oil based cloxacillin formulation and the control (n = 17) was not treated. The animals received 1 ml of the formulations, in the form of eye drops, in two applications with interval of 4 days between each. The animals underwent clinical evaluations and ocular microbiological exams. After the first and second applications, day 6 and 9 respectively, we observed a pronounced reduction of the clinical signs in the group receiving the nanostructured formulation when compared to the remaining groups (p < 0.05). There was no significant difference between the groups regarding the isolation of the agent (p = 0.85) on day 6. After the second treatment, day 9, there was no significant difference between the groups treated with the nanostructured formulation and the oil based formulation, regarding the isolation of the agent (p = 0.07), but there was difference between the group treated with the nanostructured formulation and the control (p = 0.012). The results indicate that the nanostructured formulation was more effective in reducing clinical signs and bacterial load when compared to the remaining groups.